Upper Pleistocene and Holocene Storm Deposits Eroded from the Granodiorite Coast on Isla San Diego (Baja California Sur, Mexico) - Ginni Callahan; Markes E. Johnson; Rigoberto Guardado-France; Jorge Ledesma-Vázquez (Journal of Marine Science and Engineering, 2021)
This project examines the role of hurricane-strength events likely to have exceeded 119 km/h in wind speed that entered the Gulf of California from the open Pacific Ocean during Late Pleistocene and Holocene times to impact the granodiorite shoreline on Isla San Diego. Conglomerate dominated by large, ellipsoidal to subspherical boulders at the islands south end were canvassed at six stations. A total of 200 individual cobbles and boulders were systematically measured in three dimensions, providing the database for analyses of variations in clast shape and size. The project’s goal was to apply mathematical equations elaborated after Nott (2003) with subsequent refinements to estimate individual wave heights necessary to lift igneous blocks from the joint-bound and exfoliated coast on Isla San Diego. On average, wave heights on the order of 3 m are calculated as having impacted the Late Pleistocene rocky coastline on Isla San Diego during storms, although the largest boulders more than a meter in diameter are estimated to weigh two metric tons and would have required waves in excess of 10 m for extraction. Described for the first time, a fossil marine biota associated with the boulder beds confirms a littoral-to-very-shallow water setting correlated with Marine Isotope Substage 5e approximately 125,000 years ago. A narrow submarine ridge consisting, in part, of loose cobbles and boulders extends for 1.4 km to the southwest from the island’s tip, suggesting that Holocene storms continued to transport rock debris removed from the shore. The historical record of events registered on the Saffir–Simpson Hurricane Wind Scale in the Gulf of California suggests that major storms with the same intensity struck the island in earlier times.